Novel approach to assessing residual biomass from pruning: A case study in Atlantic Pinus pinaster Ait. timber forests. (July 2017) - Hevia, Andrea; Crabiffosse, Alejandra; Álvarez-González, Juan Gabriel; Ruiz-González, Ana Daria; Majada, Juan
Abstract: Forestry residual biomass from pruning operations is an important, though little studied, potential resource. Residues normally remain in the stand, since tools for their accurate quantification do not exist and it has no particular end use. Traditional tree biomass estimation models consider the whole-tree, but estimating pruned biomass requires the development of more specific equations. This work provides a modelling approach for assessing biomass along the stem and the corresponding residual biomass from forest pruning, and quantitative results from different pruning intensities in Pinus pinaster Ait. are presented. Two types of models were considered: allometric biomass equations (whole-tree) and biomass ratio equations (tree by height along the stem), and the 2-parameter Weibull distribution function resulted in the best characterization. Diameter at breast height was the best explanatory variable in all equations, and model accuracy increased when models were combined with total tree height for the tree stem and thicker branches, or with crown ratio for the remaining tree crown components. This study provides a powerful tool to estimate residual pruned biomass, enabling its better management as a valuable source of bioenergy, as well as the importance in nutrient balance and fire risk which it plays in a sustainable forestry production. Highlights: Final models combine allometric equations and Weibull probability density function. Biomass equations by height along the stem allow accurate estimation of pruned biomass. Model can be adapted to ascertain residual biomass from different pruning intensities. Work provides a valuable tool to manage processing of residual pruned biomass.